Additive manufacturing of SS316L-IN718 superalloy Bi-metallic structure: interfacial microstructure and mechanical properties - Narayanaswamy S.; Telasang G.; Park N.; Bathe R. (My University, 2025)
The bi-metallic structure, combining AISI 316L stainless steel (SS316L) and Inconel 718 (IN718) superalloy, has many applications, including nuclear, power, and gas turbine industries. However, joining these two materials using traditional welding processes was found challenging. Therefore, this study employed a laser-based powder bed fusion of metals (PBF-LB/M) additive manufacturing technique to manufacture the SS316L-IN718 superalloy bi-metallic structure by building the SS316L part on the IN718 superalloy plate. The PBF-LB/M built bi-metallic structure was systematically characterized for its microstructure, texture, mechanical properties, and interface bonding mechanism at different length scales. The additively manufactured SS316L (AMed SS316L) part exhibited distinct microstructural features, including fine and coarse grain structures. A gradient in composition and microstructural development across the SS316L-IN718 superalloy bi-metallic interface containing a mixture of equiaxed grains, twin boundaries, and large columnar structure and cellular substructure at different length scales. In addition, randomly oriented grains in the AMed SS316L near the interface region were observed. The substrate texture of the IN718 superalloy plate does not appear to significantly influence the overall microstructure and texture formation in AMed SS316L. The additively manufactured bi-metallic structure showed peak hardness at the interface. During tensile testing, the bi-metallic tensile samples failed on the softer AMed SS316L side, away from the interface, indicating the formation of a stronger additively manufactured SS316L-IN718 superalloy bi-metallic interface. The ultimate tensile strength (UTS) recorded for the samples (550 ± 30 MPa) falls within the range of strengths observed for AMed SS316L built by PBF-LB/M samples. The enhancement in hardness and tensile properties of the additively manufactured SS316L-IN718 superalloy bi-metallic interface might be ascribed to the formation of fine-grain gradient microstructures and gradual variation in composition across the interface. © The Author(s), under exclusive licence to Springer Nature Switzerland AG 2025.